Research progress on Th17 and T regulatory cells and their cytokines in regulating atherosclerosis - Wang, Qiong; Wang, Yurong; Xu, Danyan (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary heart disease due to atherosclerosis is the leading cause of death worldwide. Atherosclerosis is considered a chronic inflammatory state in the arterial wall that promotes disease progression and outcome, and immune cells play an important role in the inflammatory process. Purpose We review the mechanisms of CD4+ T subsets, i.e., helper T17 (Th17) cells and regulatory T cells (Tregs), in regulating atherosclerosis, focusing on the role of interleukin (IL)-17, IL-10, and other cytokines in this disease and the factors influencing the effects of these cytokines. Results IL-17 secreted by Th17 cells can promote atherosclerosis, but few studies have reported that IL-17 can also stabilize atherosclerotic plaques. Tregs play a protective role in atherosclerosis, and Th17/Treg imbalance also plays an important role in atherosclerosis. Conclusion The immune response is important in regulating atherosclerosis, and studying the mechanism of action of each immune cell on atherosclerosis presents directions for the treatment of atherosclerosis. Nevertheless, the current studies are insufficient for elucidating the mechanism of action, and further in-depth studies are needed to provide a theoretical basis for clinical drug development.